The beginning and other Asian folktales - Bejarano, Valorie Slaughter; Fernandez, Estela Ocampo (PAWWA, 1995)
A collection of stories from China, India, Japan, Korea, the Philippines, Vietnam, and other Asian lands, including "Why Seawater is Salty," "The Legend of the Pinapple," "Tumbling Rice Balls," and "Hung Bu and the Raven."